2008
DOI: 10.1111/j.1601-0825.2007.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm lifestyle of Candida: a mini review

Abstract: Candida is the major fungal pathogen of humans causing a variety of afflictions ranging from superficial mucosal diseases to deep seated mycoses. Biofilm formation is a major virulence factor in the pathogenicity of Candida, and Candida biofilms are difficult to eradicate especially because of their very high antifungal resistance. Consequently, research into the pathogenicity of Candida has focused on the prevention and management of biofilm development, their architecture, and antifungal resistance. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
264
1
19

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(291 citation statements)
references
References 74 publications
7
264
1
19
Order By: Relevance
“…Similar results have been observed by Kuhn et al (2002) and Choi et al (2007). It has been suggested that biofilm resistance may be related to contributions from the extracellular matrix that prevent active drug diffusion, the physiological state of cell, efflux pumps on the cell membrane that pump antifungal drugs out of the cell or differential gene expression patterns by sessile cells (Chandra et al 2001, Kuhn et al 2002, Ramage et al 2002, Mukherjee & Chandra 2004, d'Enfert 2006, Seneviratne et al 2008. In conclusion, we observed that C. orthopsilsois and C. parapsilsosis were contaminating the water used in the haemodialysis unit studied.…”
Section: Discussionsupporting
confidence: 74%
“…Similar results have been observed by Kuhn et al (2002) and Choi et al (2007). It has been suggested that biofilm resistance may be related to contributions from the extracellular matrix that prevent active drug diffusion, the physiological state of cell, efflux pumps on the cell membrane that pump antifungal drugs out of the cell or differential gene expression patterns by sessile cells (Chandra et al 2001, Kuhn et al 2002, Ramage et al 2002, Mukherjee & Chandra 2004, d'Enfert 2006, Seneviratne et al 2008. In conclusion, we observed that C. orthopsilsois and C. parapsilsosis were contaminating the water used in the haemodialysis unit studied.…”
Section: Discussionsupporting
confidence: 74%
“…including the ability to change cell morphology, a capacity to adhere to epithelial cells as well as the potential to secrete extracellular enzymes such as phospholipases and aspartyl proteinases 6,22,35 .…”
Section: Introductionmentioning
confidence: 99%
“…36 Bacterial dental plaque is perhaps the most widely studied biofilm due to its association with caries and periodontal disease and there is increasing interest in the nature of biofilms formed by Candida spp. 37 It is widely recognised that both the biofilm structure and the phenotype of cells within a biofilm can afford protection against both host defence processes and administered antimicrobial agents. 36,38 Enhanced resistance of a biofilm to an antimicrobial has been related to failure of the agent to diffuse the biofilm, sequestering of the agent within the biofilm matrix, and the presence of persister cells within the biofilm that have a low activity status that promotes their survival in the presence of an antimicrobial.…”
Section: Discussionmentioning
confidence: 99%